Basic life support knowledge among Swiss conscripts: a national multicentre survey (Swiss Medical Weekly, 2022)
BACKGROUND: Basic life support (BLS) is the first link in the chain of survival and should be performed by every lay rescuer. Although international studies have suggested that BLS knowledge was poor among the overall population, Swiss data are scarce. Our objective in this study was to evaluate BLS knowledge among Swiss conscripts, a semi-representative sample of Swiss young adults, during the recruitment process and to identify potential characteristics related to performance.METHODS: A short online voluntary anonymous survey was proposed to Swiss conscripts called to duty in the six national recruiting centres of the Swiss Armed Forces during an 8-month period (2 February 2019 to 27 September 2019). The survey was available in three official languages (French, German, and Italian). Considered outcome was BLS knowledge evaluated on a Likert scale from 1 (very bad) to 6 (excellent). Univariate and multivariate ordinal logistic regression analyses were performed to assess the relationship between BLS knowledge and participants’ characteristics.RESULTS: Among the 19,247 conscripts called to service during the study period, 737 replied to the survey. Among them, 735 were included in the analyses (mean age 19.8 years [± 2.1]). Of these, 144 (20%) had never received any BLS training. The BLS knowledge survey was completely answered by 670 participants (91%). 157 participants (23%) reached a BLS knowledge score ≥5. Out of 695 answers, 142 (20%) did not know the Swiss emergency phone number. Out of 670 answers, 364 (54%) believed that CPR could worsen the health status of a person in cardiac arrest, whereas 413 (62%) agreed that BLS training should be mandatory in secondary school. German as native language (odds ratio [OR] 1.3, 95% confidence interval [CI] 1.0–.8)], receipt of BLS training (OR  3.1, 95% CI 2.0–4.8), and female gender were associated with a higher BLS knowledge score. Time since the last BLS training of ≥3 years (OR 0.5, 95% CI 0.4–0.7) and unemployment (OR 0.3, 95% CI 0.1–0.9) were associated with a lower BLS knowledge score. We found substantial agreement between conscripts’ scores and their self-assessments (weighted kappa with 74% agreement).DISCUSSION AND CONCLUSION: Knowledge of the emergency phone number and BLS principles was poor among Swiss conscripts participating in the study. However, their awareness and motivation is high. The effect of training during boot camp should be evaluated in further studies. Focusing on BLS training is essential and should be promoted in educational and professional contexts.